Induced crystallization on tellurite 20Li(2)O-80TeO(2) glass - Idalgo, E.; Araujo, E. B. (Iop Publishing Ltd, 2007)
Crystallization kinetics and structure of 20Li(2)O-80TeO(2) glasses are studied using x-ray diffraction, Fourier transform infrared spectroscopy and differential scanning calorimetry techniques. XRD results show gamma-TeO2, alpha-TeO2 and Li2Te2O5 phase crystallization in the glass matrix. The infrared band structure of this glass is similar to that observed in glassy TeO2. Activation energies were evaluated from Lorentzian three-peak deconvolution of the DSC crystallization peak recorded at different particle sizes. As the obtained activation values were very close, it was not possible to establish a hierarchy on the crystallization of this glass. In addition, the height of the Lorentzian peaks ( delta T-P1, delta T-P2 and delta T-P3) for each sample was measured and plotted against the nucleation temperature. The presence of two maxima at around 284 and 304 degrees C suggests at least two maximum nucleation temperatures in the studied 20Li(2)O-80TeO(2) glass.